CLINICOHISTOPATHOLOGICAL STUDY OF TESTICULAR TUMOURS IN DR. HASAN SADIKIN GENERAL HOSPITAL BANDUNG - Rindra Rizqyahya Retossa; Yantisetiasti, Anglita; Gita Tiara Dewi Nasution; Ahmad Agil; Muhammad Hasan Bashari (Indonesian Journal of Urology, 2024)
Objective: The purpose of this research was to describe the clinical and histopathological characteristics of testicular tumours at Hasan Sadikin General Hospital (RSHS) between 2017-2021. Material & Methods: This research was a cross-sectional descriptive study examining the clinical and histopathological profiles of testicular tumours. The secondary data sources included medical records from the Department of Urology, Anatomic Pathology, Medical Records, and Hospital Information System (SIRS). The collected data covered age, ethnicity, clinical symptoms, site, stage, annual prevalence rate, and analyzed using Microsoft Excel. Results: There were 42 patients who had primary testicular tumour. The highest prevalence of testicular tumours at RSHS was in 2019 consist of 12(29%) patients and the lowest in 2020 were 6(14%) patients. Most patients were >35 years old amounting 19(45%) patients, Sundanese ethnicity were 29(69%) patients, and testicular enlargement revealed in 27(64%) patients. Majority patients were in stage 0/IB 36(86%) patients and occurred in unilateral testis which 34(80%) patients, with 3(7%) patients metastasized. The most common histopathological type was seminoma 18(43%) cases followed by prepubertal-type yolk sac tumour 9(21%) patients. Seminomas, and the fibroma-thecoma group were mostly in patients over 35 years old, while prepubertal-type yolk sac tumour was more commonly in children under 15 years old. Conclusion: Prevalence of testicular tumours increased from 2017 to 2019, then started to decrease in 2020. Histopathologically, seminoma was the most common type. These tumours were most commonly found in older individuals (>35 YO) and unilateral, diagnosed in stage 0/IB, and were mostly presented with enlargement of testis. Keywords: Testicular tumours, clinical features, histopathology